2017
DOI: 10.1128/aac.02696-16
|View full text |Cite
|
Sign up to set email alerts
|

Importance of the Exopolysaccharide Matrix in Antimicrobial Tolerance of Pseudomonas aeruginosa Aggregates

Abstract: Pseudomonas aeruginosa is an opportunistic pathogen that can infect the lungs of cystic fibrosis (CF) patients and persist in the form of antibiotic-tolerant aggregates in the mucus. It has recently been suggested that such aggregates are formed due to restricted bacterial motility independent of the production of extracellular matrix components, and that they do not rely on an extracellular matrix for antimicrobial tolerance. However, we show here that biofilm matrix overexpression, as displayed by various cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
67
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 81 publications
(70 citation statements)
references
References 23 publications
2
67
1
Order By: Relevance
“…Indeed, the increased survival rates seen for P. aeruginosa cultures inoculated directly from colonies on plates are in accordance with the findings that these cultures had more aggregated biomass and that tobramycin, an antibiotic known for killing actively growing cells (35), failed to kill parts of nonattached aggregates (25). Therefore, it is likely that the increased tobramycin tolerance of cultures inoculated using method 2 is a result of cells being protected either due to reduced metabolic activity in parts of the larger aggregated population or as a result of Psl providing a shielding effect against tobramycin (36,37). This hidden difference in antibiotic tolerance among macroscopically identical cultures could have major effects on the outcomes of various studies; for example, this could be the case in susceptibility testing of antimicrobial agents, where aggregation in cultures may induce various fractions of tolerant cells.…”
Section: Discussionsupporting
confidence: 81%
“…Indeed, the increased survival rates seen for P. aeruginosa cultures inoculated directly from colonies on plates are in accordance with the findings that these cultures had more aggregated biomass and that tobramycin, an antibiotic known for killing actively growing cells (35), failed to kill parts of nonattached aggregates (25). Therefore, it is likely that the increased tobramycin tolerance of cultures inoculated using method 2 is a result of cells being protected either due to reduced metabolic activity in parts of the larger aggregated population or as a result of Psl providing a shielding effect against tobramycin (36,37). This hidden difference in antibiotic tolerance among macroscopically identical cultures could have major effects on the outcomes of various studies; for example, this could be the case in susceptibility testing of antimicrobial agents, where aggregation in cultures may induce various fractions of tolerant cells.…”
Section: Discussionsupporting
confidence: 81%
“…Previous studies have also observed nonattached aggregates in otitis media, nonhealing wounds, and soft tissue fillers (9,10). These aggregates share characteristics with surface-attached biofilms, such that they are also highly resilient to both antimicrobial treatment and host immune responses (15)(16)(17)(18)(19)(20). The aggregate phenotype is not unique to P. aeruginosa and has been described for Achromobacter, Borrelia spp., Mycobacterium abscessus, Staphylococcus aureus, Staphylococcus epidermidis, and Vibrio cholerae in a multitude of in vitro and in vivo systems (21)(22)(23)(24)(25)(26).…”
mentioning
confidence: 83%
“…Although P. aeruginosa isolates from cystic fibrosis patients produce alginate constitutively [18], loss of alginate production does not affect biofilm growth [19]. However, Pel, Psl and alginate do increase the survival of bacteria during infection [20][21][22].…”
Section: Introductionmentioning
confidence: 99%